A NOVEL SCHEDULING APPROACH FOR PILGRIM FLIGHTS OPTIMIZATION PROBLEM - Shambour, Mohd Khaled; A. Khan, Esam (Malaysian Journal of Computer Science, 2022)
The main goal of airport administrations around the world is to facilitate the conduct of passenger services and reduce waiting time as much as possible. This can be achieved by regulating the flow of passengers at the various stages of the airport, including arrival and departure halls, passport checkpoints, luggage handling, and customs. This study focuses on improving the flow of passengers in the Hajj terminal at King Abdulaziz International Airport (KAIA) in the Kingdom of Saudi Arabia, as it is one of the most welcoming stations for travelers during the Hajj season and is the fourth largest passenger terminal in the world. Three different optimization algorithms are applied to improve the scheduling process of assigning the arrival flights to available airport gates, as well as the stages inside the various airport lounges and areas. These algorithms are genetic algorithm (GA), harmony search algorithm (HSA), and differential evolution algorithm (DEA). The results give a prior knowledge of how the whole passengers’ arrival process and show the stages that are prone to congestion and cause process delay. Experimental performance results in terms of fitness value and convergence rate show that GA outperforms HSA and DEA when the population size is equal to 5, whereas DEA provides better performance compared to other algorithms when the population size is equal to 20 and 50. Moreover, the results show that the largest waiting time for passengers was in the arrival gate lounges due to the lack of allocated spaces in the passport areas, followed by the luggage area, then the passport control and customs areas, respectively.